A linguagem escrita na pré-escola pela ótica docente: uma análise do Ciclo de Políticas na rede municipal de Rio Claro/SP - Gianez, Marina (2019)
The approach of written language in early childhood education has been over the decades causing differences of opinion among scholars in the area, as well as among teachers who work in this stage of education. Although the legal guidelines point the way for teachers to follow, they are open to interpretation in the context of practice. This led us to inquire about the interpretations that are present in the daily life of classrooms regarding the learning of written language. The purpose of this qualitative research, guided by the Policy Cycle Approach, was to investigate the teachers interpretations - focusing in classes with children from 5 to 6 years old - of the current official texts regarding the written language, in Rio Claro public schools. One of the methodological procedures used for the production of research data was the semi-structured interviews conducted in focus groups with the teachers of the classes in question. For this stage of the work, one school from each of the 12 regions was selected, according to the subdivisions made by the Municipal Secretariat of Education, totaling the participation of 38 teachers. In order to understand the context of influence and the context of text production, which resulted in the elaboration of the municipal document, we conducted a semi-structured interview with the Commission Coordinator responsible for the elaboration of the Curriculum Guidance for Rio Claro Early Childhood Education and with the Coordinator of Early Childhood Education of the municipality. These interviews, associated with the teachers' focus group interviews, allowed us to understand that the origin of the document was marked by studies and disputes of ideals. Also although the participation of the entire public school network - through the coordinating teachers - was desired, it did not go as expected, as many coordinating teachers did not share information about the document with their group of teachers. Besides that, we analysed the document of the schools to which the teachers participating in the research were linked (Pedagogical Political Project), as well as their respective documents (Annual Planning and Logbook).The information found in the documents was validated through focus group interviews and analysis of children's material (notebook activities, separate sheets and portfolios) in the context of school practice. According to the analysis of the research data, it was possible to verify four different interpretations of the same official text (Curriculum Guidance of Early Childhood Education of Rio Claro) about the work to be developed with the young children. According to which, the written language in the Early Childhood Education must: prepare for entry into Elementary School through mechanical practices and exercises that enable the memorization of letters and words; emphasize the social aspect of the child in the acquisition of the alphabetic writing system; prioritize the understanding of the social function of writing; and finally, to promote the initiative and exploration of the language written by the children. These different interpretations of the same official text, found in the context of school practice, lead us to reflect on the influence of teachers' experiences and conceptions on their pedagogical practices. Thus, the data produced in this research can serve for discussions in the area, as well as enable the municipality to understand the different interpretations of working with written language in early childhood education. From this understanding, the municipality can also propose collective actions aimed at improving the quality of public education offered to the young children.